Swiss Adult Congenital HEart disease Registry (SACHER) – rationale, design and first results (Swiss Medical Weekly, 2017)
BACKGROUND In 2013, a prospective registry for adults with congenital heart disease (CHD) was established in Switzerland, providing detailed data on disease characteristics and outcomes: Swiss Adult Congenital HEart disease Registry (SACHER). Its aim is to improve the knowledge base of outcomes in adults with CHD. The registry design and baseline patient characteristics are reported. METHODS All patients with structural congenital heart defects or hereditary aortopathies, followed-up at dedicated adult CHD clinics, are asked to participate in SACHER. Data of participants are pseudonymised and collected in an electronic, web-based, database (secuTrial®). Collected data include detailed diagnosis, type of repair procedures, previous complications and adverse outcomes during follow-up. RESULTS From May 2014 to December 2016, 2836 patients (54% male, mean age 34 ± 14 years), with a wide variety of congenital heart lesions, have been enrolled into SACHER. Most prevalent were valve lesions (25%), followed by shunt lesions (22%), cyanotic and other complex congenital heart disease (16%), diseases affecting the right heart, i.e., tetralogy of Fallot or Ebstein anomaly (15%), and diseases of the left ventricular outflow tract (13%); 337 patients (12%) had concomitant congenital syndromes. The majority had undergone previous repair procedures (71%), 47% of those had one or more reinterventions. CONCLUSION SACHER collects multicentre data on adults with CHD. Its structure enables prospective data analysis to assess detailed, lesion-specific outcomes with the aim to finally improve long-term outcomes.